“I had imagined it would be worse”—implementing a standard-based quality management system for teacher education - Biehl, Jonathan; Koerber, Rolf (Frontiers in Education, 2025)
Introducing quality management systems is often a strenuous undertaking. Work processes need to be carefully examined, organized and systematized. In the field of education, quality management usually focuses mainly on organizational procedures, while the actual quality of knowledge transfer is only minimally assessed through poorly validated evaluation tools more akin to subjective happiness scales. DIN 33459, published by the German Institute for Standardization, outlines specific quality standards regarding the requirements for educators. As part of the LFB-Labs digital project, we have worked in collaboration with several science outreach laboratories to support the implementation of quality management based on DIN 33459. Our goal was to assess the difficulty of implementing the standard and identify necessary adjustments required to ensure compliance with its criteria. To achieve this, we utilized qualitative data analysis gathered from conversations with laboratory leaders and workers as well as observations during the creation of the organization’s own quality manuals. In particular, we examined whether DIN 33459 is appropriate as a minimum benchmark for teacher training programs to address the increasing demand for quality assurance in this sector. Our findings indicate that implementing DIN 33459 required very little effort from the participating organizations, with only a few work processes needing alteration. The quality manuals developed on the basis of DIN 33459 effectively helped establish a quality management system, which helped systematize and standardize the science outreach laboratories’ work processes. Nevertheless, future research must still assess the results regarding teaching efficacy utilizing a DIN 33459-based quality management system. Finally, we also explore and assess potential pitfalls of utilizing DIN 33459 but still encourage policymakers to take adopt the standard for further use.